Transient thermal analysis of an interior permanent magnet synchronous in-wheel motor driving system. (8th August 2019) - Tan, Di; Wang, Haitao; Wang, Zhongyang; Yang, Kun; Song, Fan; Fu, Hongxun
The close integration of the in-wheel motor (IWM) driving system structure makes the space closed and narrow, and heat dissipation difficult. Meanwhile, the pursuit of high power density of the IWM leads to the increase of the loss density and the temperature of the IWM. This seriously affects the safe operation of the motor and the vehicle. In this paper, an interior permanent magnet synchronous IWM driving system is taken as the research object. The electromagnetic and temperature field analysis model are developed based on the detailed structure of the IWM driving system firstly. Then the transient thermal analysis under the rated and peak condition are carried out through the magneto-thermal coupling method. The results show that, under rated condition, when the IWM reaches a steady state, the highest temperature occurs on the copper wire of the stator winding, which is 111.8°C; under peak condition, due to the big loss generated by the motor overload operation, the maximum temperature of the motor reaches 170°C during the simulation analysis of 60 s, which has exceeded the motor insulation level requirements of 155°C. Therefore, cooling design is necessary in order to ensure the normal operation of the IWM and the vehicle.